Micro Sociological Theories And Their Function Of Aesthetics - Donie Fadjar Kurniawan (Gelar : Jurnal Seni Budaya, 2007)
Aesthetics is basically part of ore daily life. It has a very closet meaning to guide, choose and determine in our behavior and attitudes. In Micro sociology, there is also paralel and strong opinions about those, here we know as the phenomenology, ethno methodology,symbolic interaction and hermeneutics. This writing will explore how that micro sociological theories have a strategis interrelationsip among them. It can be seen clearly on the work about discourse, philosophical anthropological, and psiycho analytic theory of arts.Keywords : Micro sociological theories, aesthetics of art